World Language Medical Interpretation Courses in Nursing: Reasons For Incorporating, Diversifying and Implementing Medical Terminology Courses (Global Journal of Human-Social Science, 2023)
ABSTRACT Background The inclusion of world language medical language interpretation into nursing education can be vital for nursing student s development future job satisfaction and patient care This research addressed the importance of adding medical language interpretation courses to nursing and other healthcare professions why students and healthcare workers decided to enroll complete and or exit these courses and what kind of resources would be beneficial to help students achieve success
Keywords: medical spanish; applied linguistics; spanish service-learning; medical interpretation; spanish heritage speakers